Impact of concurrent splenectomy and esophagogastric devascularization on surgical outcomes of partial hepatectomy for hepatocellular carcinoma in patients with clinically significant portal hypertension: A multicenter propensity score matching analysis. Issue 5 (May 2022) - Chen, Zheng-Liang; Yao, Lan-Qing; Pu, Jia-Le; Wu, Han; Xu, Xin-Fei; Chen, Ting-Hao; Zhou, Ya-Hao; Wang, Hong; Chen, Zhi-Yu; Sun, Li-Yang; Diao, Yong-Kang; Zhong, Jian-Hong; et al.
Abstract: Purpose: Portal hypertension due to cirrhosis is common among patients with hepatocellular carcinoma (HCC). This study aimed to compare the outcomes of partial hepatectomy in patients with HCC and clinically significant portal hypertension (CSPH) with or without concurrent splenectomy and esophagogastric devascularization (CSED). Patients and methods: From a multicenter database, patients with HCC and CSPH who underwent curative-intent hepatectomy were identified. Postoperative morbidity and mortality, and long-term overall survival (OS) were compared in patients with and without CSED before and after propensity score matching (PSM). Results: Of the 358 enrolled patients, 86 patients underwent CSED. Before PSM, the postoperative 30-day morbidity and mortality rates were comparable between the CSED and non-CSED group (both P > 0.05). Using PSM, 81 pairs of patients were created. In the PSM cohort, the 5-year OS rate of the CSED group were significantly better than the non-CSED group (52.9% vs . 36.5%, P = 0.046). The former group had a significantly lower rate of variceal bleeding on follow-up (7.4% vs . 21.7%, P = 0.014). On multivariate analysis, CSED was associated with significantly better OS (HR: 0.39, P < 0.001). Conclusion: Hepatectomy and CSED can safely be performed in selected patients with HCC and CSPH, which could improve postoperative prognosis by preventing variceal bleeding, and prolonging long-term survival.